Online Innovation and Buyback Intent In The Training Industry: The Mediating Effect with Customer Experience - Claudio Chandra Setiawan; Ina Agustini Murwani (CV. Syntax Corporation Indonesia, 2024)
This study aims to investigate the role of customer experience as a mediator in the relationship between online innovation and repurchase intention in the training industry in Indonesia. In the context of intense competition, understanding the factors that influence consumers' intention to repurchase is crucial for business continuity. Data was collected through a survey involving 274 respondents who had participated in training, both online and offline. Respondents were selected based on predetermined criteria. Data analysis was conducted using structural equation modeling (SEM) to evaluate the relationships between variables, including online innovation, customer experience, and repurchase intentions. The research findings show that online innovation does not have a significant direct influence on repurchase intentions. However, customer experience was shown to have a positive and significant impact on repurchase intentions. In other words, customer experience plays an important role as a mediator linking online innovation with consumers' intention to repurchase in the context of training. This study has limitations, as it only considers the customer perspective. Further research is recommended to explore the company's point of view and other variables that may contribute to repurchase intentions. The findings emphasize that training companies need to prioritize improving customer experience to increase retention rates and profitability. Overall, the results of this study suggest that while online innovation is important, the main focus should be on developing a positive customer experience to drive repurchase intentions. This is a key strategy for companies to face challenges in the increasingly competitive training industry.